Finite Element Analysis Study of the Effect of Superstructure Material on Stress Distribution in an Implant-Supported Fixed Prosthesis - (:unkn) unknown (My University, 1997)
This study used three-dimensional finite clement analysis to investigate the effect of three different occlusal surface materials (resin, resin composite, and porcelain) and four different framework materials (gold, silver-palladium, cobalt-chromium, titanium alloys) on the stress distribution in a six-implant-supported mandibular fixed prosthesis and surrounding bone. A total of 172 N vertical load was distributed over the entire occlusal surface of the finite element model. Generated stress values were calculated in the occlusal surface material, framework, prosthesis retaining screws, implants, and surrounding cortical and spongy bones. The results obtained demonstrated that using a prosthesis superstructure material with a lower elastic modulus (1) did not lead to substantial differences in stress patterns nor in values at the cortical and spongy bones surrounding the implants; and (2) concentrated stresses in the retaining screws for the prosthesis and thus increased the potential risk of prosthesis failure. For the single loading condition investigated, the optimal combination of materials was found to be cobalt-chromium for the framework and porcelain for the occlusal surface.